Topic Trend Analysis of Postgraduate Theses on Organizational Commitment in the Field of Education - Biber, Emine Didem (Kastamonu Egitim Dergisi, 2025)
Purpose: The purpose of this research is to conduct topic trend analyses of postgraduate theses addressing the subject of "organizational commitment" in education. Design/Methodology/Approach: In the study, the document review method was used to describe and interpret the tendencies of the theses in depth. The data required for the research was generated from the theses with the help of a form created by the researcher. Of the 403 theses scanned this way, 45 were doctoral, and 358 were master's. Findings: As a result of the analyses, it was determined that the first theses on the subject were completed in 2004. Foundation universities were ahead in the number of master's theses, but doctoral theses in foundation universities were almost nonexistent. In addition, it was observed that in nearly all the theses designed in relational screening, teachers and principals were preferred as the sample group, and primary and secondary schools were selected as the study field. The main factors affecting organizational commitment discussed in the theses were classified as "organizational climate," "individual factors," and "manager." These factors were distributed evenly in the theses. Highlights: Organizational commitment is a fundamental concept for educational organizations. It is essential to examine how the subject of “organizational commitment” is addressed in the field of education in postgraduate theses whose scientific validity and reliability have been approved in terms of depth and scope.
Keywords: Eğitim Yönetimi; Education Management; Organizationalcommitment; Education; Management; Topic trend analysis